2010
DOI: 10.1039/b917298j
|View full text |Cite
|
Sign up to set email alerts
|

Fate and removal of estrogens in municipal wastewater

Abstract: Natural and synthetic estrogens are some of the most potent endocrine disrupting compounds found in municipal wastewater. Much research has been conducted on the source and fate of estrogens in wastewater treatment plants. Sorption and biodegradation are the primary removal mechanisms for estrogens in activated sludge systems, which are widely used biological treatment techniques for municipal wastewater treatment. However, when removal of estrogens in a wastewater treatment plant is incomplete, these compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 232 publications
(410 reference statements)
1
66
0
1
Order By: Relevance
“…The sorbent specific characteristics of the sludge and the experimental conditions largely affected the estrogen removal results, corresponding with the results of Chen and Hu (2010), Racz and Goel (2010) and Silva et al (2012). This finding could explain the sorption variability that was observed among the different studies.…”
Section: Activated and Deactivated Sludgesupporting
confidence: 59%
See 2 more Smart Citations
“…The sorbent specific characteristics of the sludge and the experimental conditions largely affected the estrogen removal results, corresponding with the results of Chen and Hu (2010), Racz and Goel (2010) and Silva et al (2012). This finding could explain the sorption variability that was observed among the different studies.…”
Section: Activated and Deactivated Sludgesupporting
confidence: 59%
“…Generally, after fast initial adsorption on the sludge, biodegradation will reduce the estrogen levels in the aqueous and solid phases (Desmiarti and Li, 2013;Marti and Batista, 2014). According to Racz and Goel (2010), immediate estrogen losses in activated sludge, which occurred in our study, can largely be attributed to sorption.…”
Section: Activated and Deactivated Sludgementioning
confidence: 93%
See 1 more Smart Citation
“…Among these estrogens, E2 and EE2 have three to seven orders of magnitude greater estrogenic potencies than the other EDCs identified in wastewater [27]. The lowest observable effect concentration for E2 affecting production of vitellogenin in juvenile female rainbow trout is 14 ng/L [27]. Purdom and coworkers reported that less than 1 ng/L of EE2 can stimulate male rainbow trout to produce vitellogenin [28], while Lange and coworkers found that a concentration of 4 ng/L EE2 can cause failure in the male fathead minnow to develop normal secondary sexual characteristics [29].…”
Section: Introductionmentioning
confidence: 97%
“…The four estrogens most commonly found in wastewater include three natural steroids (17b-estradiol (E2), estrone (E1) and estriol (E3)) and one synthetic compound (17a-ethinylestradiol (EE2)) that is used in contraceptives and hormone replacement therapy [26]. Among these estrogens, E2 and EE2 have three to seven orders of magnitude greater estrogenic potencies than the other EDCs identified in wastewater [27]. The lowest observable effect concentration for E2 affecting production of vitellogenin in juvenile female rainbow trout is 14 ng/L [27].…”
Section: Introductionmentioning
confidence: 99%